Al-Ghazali’s Perspective on the Innate Nature of Teachers to Improve the Quality of Islamic Education - Muhammad Misbakul Munir (CV. Publikasi Indonesia, 2026)
This study is motivated by the tendency of contemporary Islamic education systems to emphasize cognitive and administrative aspects while neglecting spiritual and moral dimensions, thereby reducing the role of teachers to mere knowledge transmitters. This research aims to examine the concept of teacher’s fitrah from the perspective of Abu Hamid al-Ghazali and its relevance in improving the quality of Islamic education. The study employs a qualitative approach using library research, with primary data derived from Al-Ghazali’s works and secondary data from relevant academic literature. Data analysis is conducted through content analysis and a hermeneutic approach to interpret the meaning of texts comprehensively. The research gap lies in the limited number of studies that position teachers as subjects possessing their own fitrah that requires continuous development, rather than focusing solely on students. The findings reveal that teacher’s fitrah encompasses spiritual, moral, and intellectual potentials that must be actualized through self-purification (tazkiyat al-nafs), exemplary conduct, and holistic competence development. The implementation of this concept leads to a paradigm shift in education, strengthens teacher character, and enhances the quality of learning interactions. Teacher’s fitrah becomes a fundamental element in constructing an integrative, value-oriented, and sustainable Islamic education system.